Silicone adhesive laminated polyester film
A laminated polyester film with a cured resin layer containing specific crosslinking agents and polyester resin is used to enhance adhesion to silicone adhesive layers, addressing issues of excessive adhesive strength and interference with silicone hardening, and achieving reliable bonding.
Patent Information
- Application Number
- JP2021022665
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-02-16
Smart Images

Figure 0007666005000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated polyester film for silicone adhesion and a film laminate using the same. [Background technology]
[0002] Polyester films have excellent properties such as mechanical strength, dimensional stability, flatness, heat resistance, chemical resistance, and optical properties, and also have excellent cost performance, and therefore are used in a variety of applications.
[0003] Conventionally, silicone adhesive layers, which have excellent transparency and durability, have been used for various applications such as displays as a method for bonding optical components together. When a resin film is used as an optical member, it may be incorporated into a display in a state where it is attached to a silicone adhesive layer. In this case, it is required that the optical member does not easily peel off from the silicone adhesive layer in situations where peeling is not actually necessary, and that the adhesion to the silicone adhesive layer is particularly good. Therefore, methods for improving adhesion from the adhesive layer side have also been proposed. For example, Patent Document 1 describes the provision of a film suitable for application to flat panel displays, which does not trap air bubbles during application, does not shift or peel off by itself after application, but is easy to peel off by hand, and a pressure-sensitive adhesive composition for the film. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-152266 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when trying to improve the adhesion from the silicone adhesive layer side, the adhesive strength tends to increase, and it is sometimes difficult to obtain the desired adhesive strength. Furthermore, when an easy-adhesion layer is provided on the surface of the resin film, the curing property of the silicone adhesive layer may be affected depending on the constituent material of the easy-adhesion layer. For this reason, there was a need for a resin film provided with an easy-adhesion layer with good adhesion that would not cause inhibition of curing when the silicone adhesive layer is cured, and yet would be able to exhibit the adhesive properties that the silicone adhesive layer originally possesses. The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a novel laminated polyester film that has good adhesion to a silicone adhesive layer. [Means for solving the problem]
[0006] In view of the above circumstances, the present inventors have conducted extensive research and found that the above problems can be easily solved by using a laminated polyester film having a specific structure, and have completed the present invention. That is, the present invention provides the following items [1] to
[15] .
[0007] [1] A laminated polyester film for silicone adhesion, comprising a polyester film and, on at least one surface thereof, a cured resin layer comprising a cured resin layer composition containing the following compounds (A) and (B): (A) At least one crosslinking agent selected from the group consisting of epoxy compounds and carbodiimide compounds. (B) A polyester resin having a glass transition temperature (Tg) of 0°C or higher. [2] The laminated polyester film for silicone adhesion according to the above [1], wherein the cured resin layer composition further comprises at least one compound selected from the group consisting of oxazoline compounds and melamine compounds. [3] The laminated polyester film for silicone adhesion according to the above [1] or [2], wherein the compound (B) is a polyester resin containing, as an acid component, a dicarboxylic acid component having 10 or less carbon atoms. [4] The laminated polyester film for silicone adhesion according to any one of the above [1] to [3], wherein the compound (B) is a polyester resin containing, as a diol component, ethylene glycol and at least one selected from 1,4-butanediol, diethylene glycol and triethylene glycol. [5] The laminated polyester film for silicone adhesion according to any one of the above [1] to [4], wherein the compound (B) is a polyester resin containing a polycyclic compound as an acid component. [6] The laminated polyester film for silicone adhesion according to any one of the above [1] to [5], wherein the compounding ratio (A) / (B) (mass ratio) of the compounds (A) and (B) is 10 / 90 to 50 / 50. [7] A film laminate in which another resin film or a glass substrate is laminated onto the cured resin layer of the laminated polyester film according to any one of the above [1] to [6] via a silicone adhesive layer. [8] The film laminate according to the above [7], wherein the other resin film is selected from the group consisting of a polyester film, a polyimide film, and a cyclic polyolefin film. [9] The film laminate described in either [7] or [8] above, wherein a functional layer is provided on the surface of the other resin film that contacts the silicone adhesive layer.
[10] The film laminate described in [9] above, wherein the functional layer is a release layer.
[11] The film laminate according to the above
[10] , wherein the release layer is a release layer containing at least one selected from the group consisting of a curable silicone resin, a fluorine-based compound, and a long-chain alkyl compound.
[12] The film laminate according to any one of the above [7] to
[11] , having a total thickness of 200 μm or less.
[13] The pressure-sensitive adhesive laminated polyester film according to any one of the above [1] to [6], which is for use in a display.
[14] The film laminate according to any one of the above [7] to
[13] , which is for use in a display.
[15] The film laminate according to
[14] above, which is for mounting on a vehicle. Effect of the Invention
[0008] According to the present invention, a laminated polyester film having good adhesion to a silicone adhesive layer can be provided, and its industrial utility value is high.
Embodiment for Carrying Out the Invention
[0009] Hereinafter, an example of an embodiment of the present invention will be described in detail. However, the present invention is not limited to the embodiments described below, and can be arbitrarily modified and implemented without departing from the gist of the present invention. In this specification, the term "A to B" regarding the description of numerical values means "A or more and B or less" (when A < B) or "A or less and B or more" (when A > B). In the present invention, a combination of preferred embodiments is a more preferred embodiment. In this specification, when the expression "(meth)acrylic acid" is used, it means one or both of "acrylic acid" and "methacrylic acid". Similarly, "(meth)acrylate" means one or both of "acrylate" and "methacrylate", and "(meth)acryloyl" means one or both of "acryloyl" and "methacryloyl".
[0010] The laminated polyester film for silicone adhesion of the present invention is provided with a cured resin layer containing a cured resin layer composition containing the following compounds (A) and (B) on at least one surface of the polyester film. (A) At least one crosslinking agent selected from the group consisting of an epoxy compound and a carbodiimide compound. (B) A polyester resin having a glass transition temperature (Tg) of 0°C or higher.
[0011] <Polyester Film> The polyester film (substrate) constituting the laminated polyester film may have a single layer structure or a multilayer structure. In the case of a multilayer structure, it may have a two-layer structure, a three-layer structure, or a four-layer structure or more, as long as it does not deviate from the gist of the present invention, and the number of layers is not particularly limited. In addition, as the polyester film, a biaxially oriented polyester film is preferable from the viewpoints of thinning and dimensional stability.
[0012] The polyester used may be a homopolyester or a copolymer polyester. In the case of a homopolyester, it is preferable that the polyester is obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid, and examples of the aliphatic glycol include ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol. A representative polyester is polyethylene terephthalate. On the other hand, examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, and oxycarboxylic acid, and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 4-cyclohexanedimethanol, and neopentyl glycol.
[0013] The polyester polymerization catalyst is not particularly limited, and any conventionally known compound can be used, such as titanium compounds, germanium compounds, antimony compounds, manganese compounds, aluminum compounds, magnesium compounds, and calcium compounds.
[0014] In order to suppress the amount of oligomer component precipitation, the film may be produced using a polyester with a low content of oligomer component as a raw material. As a method for producing a polyester with a low content of oligomer component, various known methods can be used, for example, a method of performing solid-phase polymerization after polyester production. In addition, the amount of oligomer component precipitation may be suppressed by forming a polyester film with a structure of three or more layers and making the outermost layer of the polyester film a layer using a polyester raw material with a low content of oligomer component. In addition, the polyester may be obtained by melt polycondensation under reduced pressure at a higher reaction temperature after esterification or ester exchange reaction.
[0015] It is also possible to incorporate an ultraviolet absorbing agent into the polyester film in order to improve the weather resistance of the film and prevent deterioration of the adherend (e.g., liquid crystal), etc. The ultraviolet absorbing agent is a compound that absorbs ultraviolet light and is not particularly limited as long as it can withstand the heat applied during the manufacturing process of the polyester film.
[0016] As the ultraviolet absorbing agent, there are organic ultraviolet absorbing agents and inorganic ultraviolet absorbing agents, and from the viewpoint of transparency, organic ultraviolet absorbing agents are preferred.As the organic ultraviolet absorbing agent, there are no particular limitations, but for example, cyclic imino esters, benzotriazoles, benzophenones, etc. are mentioned.From the viewpoint of durability, cyclic imino esters and benzotriazoles are more preferred.In addition, it is also possible to use two or more kinds of ultraviolet absorbing agents in combination.
[0017] It is also possible to incorporate particles into the polyester film for the main purpose of imparting easy slippage and preventing scratches during each process. The type of particles to be incorporated is not particularly limited as long as it is a particle capable of imparting easy slippage, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenolic resin, epoxy resin, and benzoguanamine resin. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process can also be used.
[0018] The shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. may be used. There are also no particular limitations on the hardness, specific gravity, color, etc. Two or more types of these particles may be used in combination as necessary.
[0019] The average particle size of the particles used is usually 5 μm or less, preferably in the range of 0.01 to 3 μm. If it is 5 μm or less, the surface roughness of the film does not become too rough, which is preferable since it does not cause problems when various surface functional layers are formed in a later process.
[0020] Furthermore, the particle content in the polyester film is usually less than 5% by mass, preferably in the range of 0.0003 to 3% by mass. When there are no particles or only a small amount of particles, the film has high transparency and is a good film, but the slipperiness may be insufficient, so it may be necessary to take measures such as adding particles to the coating layer to improve the slipperiness. Furthermore, when the particle content is less than 5% by mass, the transparency of the film can be sufficiently guaranteed. When particles are contained, for example, it is preferable to provide a surface layer and an intermediate layer and to contain particles in the surface layer. In this case, it is more preferable to form a multilayer structure having a surface layer containing particles, an intermediate layer, and a surface layer containing particles in this order.
[0021] The method of adding particles to the polyester film is not particularly limited, and any conventionally known method can be adopted. For example, in the case of a multi-layer polyester film, the particles can be added at any stage of manufacturing the polyester constituting each layer, but it is preferable to add the particles after the completion of the esterification or transesterification reaction.
[0022] In addition to the above-mentioned particles, conventionally known antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, etc. may be added to the polyester film as necessary.
[0023] The thickness of the polyester film is not particularly limited as long as it is within a range that allows formation of a film, but is usually in the range of 10 to 350 μm, preferably 25 to 250 μm, and more preferably 38 to 125 μm.
[0024] Next, a specific example of the production of a polyester film will be described, but the production is not limited to the following production example. For example, when producing a biaxially stretched polyester film, a method is preferred in which the dried pellets of the polyester raw material described above are extruded as a molten sheet from a die using an extruder, and cooled and solidified with a cooling roll to obtain an unstretched sheet. In this case, it is preferred to increase the adhesion between the sheet and the rotating cooling drum in order to improve the flatness of the sheet, and an electrostatic application adhesion method and / or a liquid application adhesion method are preferably used. Next, the obtained unstretched sheet is stretched in biaxial directions. In this case, the unstretched sheet is first stretched in one direction by a roll or tenter type stretching machine. The stretching temperature is usually 70 to 120°C, preferably 80 to 110°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times. Next, the sheet is stretched in a direction perpendicular to the first-stage stretching direction, in which the stretching temperature is usually 70 to 170°C, and the stretching ratio is usually 3.0 to 7 times, preferably 3.5 to 6 times. Then, the film is subsequently heat-treated under tension or relaxation of 30% or less at a temperature of 180 to 270°C to obtain a biaxially oriented film. In the above stretching, a method of stretching in one direction in two or more stages can be adopted. In that case, it is preferable to perform the stretching so that the final stretch ratios in both directions are within the above ranges.
[0025] A simultaneous biaxial stretching method can also be used to produce the polyester film. The simultaneous biaxial stretching method involves simultaneously stretching and orienting the unstretched sheet in the machine direction and the width direction under a temperature controlled condition usually at 70 to 120° C., preferably 80 to 110° C., and the stretching ratio is preferably 4 to 50 times, more preferably 7 to 35 times, and even more preferably 10 to 25 times in terms of area ratio. Then, the film is subsequently heat-treated under tension or under relaxation of 30% or less at a temperature of 170 to 250° C. to obtain a stretched and oriented film. Regarding the simultaneous biaxial stretching device employing the above-mentioned stretching method, a conventionally known stretching method such as a screw method, a pantograph method, or a linear drive method can be employed.
[0026] <Cured resin layer composition> The laminated polyester film of the present invention has a cured resin layer on at least one surface of the polyester film, and the cured resin layer is formed from a cured resin layer composition containing the compounds (A) and (B) described below. The laminated polyester film of the present invention can improve adhesion with the silicone adhesive layer by having the cured resin layer. In addition, when forming the silicone adhesive layer on the laminated polyester film, the curing inhibition of the silicone adhesive layer can be suppressed, so that the desired adhesiveness can be obtained.
[0027] (Compound (A): Crosslinking agent) The cured resin layer composition according to the present invention must contain at least one crosslinking agent selected from the group consisting of epoxy compounds and carbodiimide compounds in order to improve adhesion between the cured resin layer and the silicone adhesive layer and to improve the durability of the cured resin layer. From the viewpoint of improving the adhesion of the silicone adhesive layer, it is preferable that the cured resin layer composition according to the present invention further contains at least one compound selected from the group consisting of oxazoline compounds and melamine compounds.
[0028] (Epoxy compounds) The epoxy compound is a compound having an epoxy group in the molecule, and examples thereof include condensations of epichlorohydrin, ethylene glycol, polyethylene glycol, glycerin, polyglycerin, bisphenol A, etc. with a hydroxyl group or an amino group, polyepoxy compounds, diepoxy compounds, monoepoxy compounds, and glycidylamine compounds. Examples of polyepoxy compounds include sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, etc. Examples of diepoxy compounds include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, etc. Examples of the monoepoxy compound include allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether, and examples of the glycidylamine compound include N,N,N',N'-tetraglycidyl-m-xylylenediamine and 1,3-bis(N,N-diglycidylamino)cyclohexane. From the viewpoint of improving adhesion, polyether-based epoxy compounds are preferred. In terms of the amount of epoxy groups, polyepoxy compounds having three or more functional groups are preferred over those having two functional groups.
[0029] (Carbodiimide compounds) A carbodiimide compound is a compound having a carbodiimide structure, and is a compound having one or more carbodiimide structures in the molecule. For better adhesion, etc., a polycarbodiimide compound having two or more carbodiimide structures in the molecule is more preferred.
[0030] Carbodiimide compounds can be synthesized by conventionally known techniques, and generally, condensation reaction of diisocyanate compounds is used. The diisocyanate compounds are not particularly limited, and both aromatic and aliphatic compounds can be used, and specific examples include tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate.
[0031] The content of carbodiimide groups contained in the carbodiimide compound, in terms of carbodiimide equivalent (weight [g] of the carbodiimide compound required to provide 1 mol of carbodiimide groups), is usually in the range of 100 to 1000, preferably 250 to 800, and more preferably 300 to 700. By using within the above range, the durability of the coating film is improved.
[0032] Furthermore, within the scope of the present invention, in order to improve the water solubility or water dispersibility of the polycarbodiimide compound, a surfactant may be added, or a hydrophilic monomer such as a polyalkylene oxide, a quaternary ammonium salt of a dialkylamino alcohol, or a hydroxyalkylsulfonate may be added.
[0033] (Oxazoline compounds) The oxazoline compound is a compound having an oxazoline group in the molecule, and in particular, a polymer containing an oxazoline group is preferred, and can be prepared by polymerization of an addition polymerizable oxazoline group-containing monomer alone or with other monomers. Examples of the addition polymerizable oxazoline group-containing monomer include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline, and one or a mixture of two or more of these can be used. Among these, 2-isopropenyl-2-oxazoline is suitable because it is easily available industrially. The other monomer is not limited as long as it is a monomer that can be copolymerized with the addition-polymerizable oxazoline group-containing monomer, and examples thereof include (meth)acrylic acid esters such as alkyl (meth)acrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrenesulfonic acid, and salts thereof (sodium salts, potassium salts, ammonium salts, tertiary amine salts, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylamide, N-alkyl (meth)acrylate, etc. Examples of the monomer include unsaturated amides such as t)acrylamide and N,N-dialkyl(meth)acrylamide (the alkyl group can be a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, a 2-ethylhexyl group, a cyclohexyl group, and the like); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride and vinylidene chloride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. One or more of these monomers can be used.From the viewpoint of improving adhesion, the amount of oxazoline groups in the oxazoline compound is preferably in the range of 0.5 to 10 mmol / g, more preferably 1 to 9 mmol / g, further preferably 3 to 8 mmol / g, and particularly preferably 4 to 6 mmol / g.
[0034] (Melamine compounds) The melamine compound is a compound having a melamine skeleton in the compound, and for example, an alkylolated melamine derivative, a compound partially or completely etherified by reacting an alkylolated melamine derivative with an alcohol, and a mixture thereof can be used. As the alcohol used for etherification, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, isobutanol, etc. are preferably used. In addition, the melamine compound may be either a monomer or a dimer or higher polymer, or a mixture thereof may be used. Furthermore, a product obtained by co-condensing a part of melamine with urea or the like can also be used, and a catalyst can be used to increase the reactivity of the melamine compound.
[0035] (Other crosslinking agents) Within the scope of the present invention, other crosslinking agents may be used in combination, for example, in an amount of 5% by mass or less, preferably 3% by mass or less, based on the non-volatile components in the cured resin layer.
[0036] (Isocyanate compounds) The isocyanate compound is a compound having an isocyanate or an isocyanate derivative structure, such as a blocked isocyanate. Examples of the isocyanate include aromatic isocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic isocyanates having an aromatic ring, such as α,α,α',α'-tetramethyl xylylene diisocyanate; aliphatic isocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic isocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isopropylidenedicyclohexyl diisocyanate. In addition, polymers and derivatives such as biuretized products, isocyanurate products, uretdione products, and carbodiimide modified products of these isocyanates are also included. These may be used alone or in combination. Among the above isocyanates, aliphatic isocyanates or alicyclic isocyanates are more preferable than aromatic isocyanates in order to prevent yellowing due to ultraviolet rays.
[0037] When used in the form of a blocked isocyanate, examples of the blocking agent include bisulfites; phenolic compounds such as phenol, cresol, and ethylphenol; alcohol compounds such as propylene glycol monomethyl ether, ethylene glycol, benzyl alcohol, methanol, and ethanol; active methylene compounds such as methyl isobutanoylacetate, dimethyl malonate, diethyl malonate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone; mercaptan compounds such as butyl mercaptan and dodecyl mercaptan; lactam compounds such as ε-caprolactam and δ-valerolactam; amine compounds such as diphenylaniline, aniline, and ethyleneimine; acid amide compounds such as acetanilide and acetic acid amide; and oxime compounds such as formaldehyde oxime, acetaldoxime, acetone oxime, methyl ethyl ketone oxime, and cyclohexanone oxime. These may be used alone or in combination of two or more.
[0038] The isocyanate compound may be used alone or as a mixture or bond with various polymers. In terms of improving the dispersibility and crosslinking property of the isocyanate compound, it is preferable to use a mixture or bond with a polyester resin or a urethane resin.
[0039] (Compound (B): Polyester resin) The polyester resin in the compound (B) may be, for example, one composed of an acid component and a diol component as the main constituent components, such as those shown below. Examples of the acid component include the following polyvalent carboxylic acids. Dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, and succinic acid; tricarboxylic acids such as trimellitic acid and trimesic acid; tetracarboxylic acids such as pyromellitic acid; acid anhydrides such as trimellitic anhydride and phthalic anhydride; p-hydroxybenzoic acid; monopotassium trimellitic acid salt; and ester-forming derivatives thereof can be used. Examples of the diol component include the following polyhydric hydroxy compounds, and examples of the compounds that can be used include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, etc. One or more of these compounds may be appropriately selected and a polyester resin may be synthesized by a conventional polycondensation reaction. The polyester resin may be prepared as a water dispersion, and in this case, a hydrophilic functional group or the like may be appropriately introduced into the polyester resin.
[0040] In the present invention, the glass transition temperature (Tg) of the polyester resin in compound (B) must be 0° C. or higher, preferably 40° C. or higher, and more preferably 80° C. or higher. When the Tg of the polyester resin in compound (B) is within the above range, the cured resin layer has excellent solvent resistance when processing the silicone adhesive layer, and also has the advantage that the cured resin layer is less likely to fall off from the polyester film when used at room temperature.
[0041] In the present invention, from the viewpoint of improving adhesion, the polyester resin of compound (B) preferably contains, as an acid component, a dicarboxylic acid component having 10 or less carbon atoms, and more preferably a dicarboxylic acid component having 8 or less carbon atoms. The dicarboxylic acid component having 10 or less carbon atoms may be used alone or in combination of two or more kinds. As the dicarboxylic acid component, the above-listed carboxylic acids can be suitably used, and it is more preferable to use terephthalic acid, isophthalic acid, or 5-sodium sulfoisophthalic acid.
[0042] Furthermore, in the present invention, the polyester resin of compound (B) is preferably a polyester resin containing, as a diol component, ethylene glycol and at least one selected from 1,4-butanediol, diethylene glycol and triethylene glycol, from the viewpoint of improving adhesion. When the polyester resin contains the above diol component, the mass ratio of the content of ethylene glycol to the content of diol components other than ethylene glycol ([content of ethylene glycol] / [content of diol components other than ethylene glycol]) is preferably 40 / 60 to 90 / 10, more preferably 40 / 60 to 80 / 20, and even more preferably 45 / 55 to 75 / 25.
[0043] In the present invention, the compound (B) is preferably a polyester resin containing a polycyclic compound as an acid component. By containing a polycyclic compound as an acid component in the polyester resin of the compound (B), the glass transition temperature of the polyester resin can be easily increased and can be adjusted to within the above-mentioned glass transition temperature range, so that the physical properties of the cured resin layer can be made suitable. As the polycyclic compound, a polycyclic aromatic compound is preferred, a polycyclic aromatic compound having 12 or more carbon atoms is more preferred, and a polycyclic aromatic compound having a naphthalene ring is even more preferred. As the polycyclic aromatic compound, the carboxylic acids listed above can be suitably used, and it is preferred to use 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid and 2,7-naphthalenedicarboxylic acid, and it is more preferred to use 2,6-naphthalenedicarboxylic acid. The polycyclic compound may be used alone or in combination of two or more. In addition, the above-mentioned dicarboxylic acid component having 10 or less carbon atoms may be used in combination with the polycyclic compound.
[0044] (Other binder resins) Within the scope of the present invention, other binder resins may be used in combination in an amount of, for example, 5% by mass or less, preferably 3% by mass or less, based on the non-volatile components in the cured resin layer. Examples of other binder resins include (meth)acrylic resins.
[0045] ((Meth)acrylic resin) The (meth)acrylic resin is a polymer made of polymerizable monomers including acrylic and methacrylic monomers. These may be homopolymers or copolymers, or may be copolymers with polymerizable monomers other than acrylic and methacrylic monomers. The (meth)acrylic polymer is a polymer having (meth)acrylic acid or a (meth)acrylic acid alkyl ester as a constituent unit, and may be a copolymer of styrene or a styrene derivative and (meth)acrylic acid or a (meth)acrylic acid alkyl ester. Also included are copolymers of these polymers with other polymers (e.g., polyester, polyurethane, etc.), such as block copolymers and graft copolymers. That is, the (meth)acrylic resin may be a (meth)acrylic-modified polyester resin or a (meth)acrylic-modified polyurethane resin. Further, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in a polyester solution or polyester dispersion. Similarly, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in a polyurethane solution or polyurethane dispersion. Similarly, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in another polymer solution or dispersion, and these are also referred to as (meth)acrylic modified polyester resins and (meth)acrylic modified polyurethane resins in this specification. The above-mentioned polyesters and polyurethanes used in the (meth)acrylic resins can be appropriately selected from those exemplified as polyesters and polyurethanes used in the binder resins described later. The (meth)acrylic resin may contain a hydroxy group or an amino group in order to further improve the adhesion to the base film.
[0046] The polymerizable monomer is not particularly limited, but particularly representative compounds include various carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutylhydroxyfumarate, and monobutylhydroxyitaconate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, lauryl (meth)acrylate, and the like. various nitrogen-containing compounds such as (meth)acrylamide, diacetone acrylamide, N-methylolacrylamide, or (meth)acrylonitrile; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, or vinyltoluene; various vinyl esters such as vinyl propionate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, or the like; phosphorus-containing vinyl monomers; various vinyl halides such as vinyl chloride and vinylidene chloride; and various conjugated dienes such as butadiene.
[0047] (Other ingredients) In forming the cured resin layer, particles can be used in combination for the purpose of improving anti-blocking properties, slip properties, etc., within the scope of the present invention.
[0048] The proportion of compound (A) in the total non-volatile components in the resin composition is preferably 5 to 70 mass%, more preferably 15 to 60 mass%. When the proportion of compound (A) is equal to or less than the upper limit, the strength and transparency of the cured resin layer are good. On the other hand, when the proportion of compound (A) is equal to or more than the lower limit, the durability of the coating film is good and the desired adhesion can be obtained.
[0049] The proportion of compound (B) in the total non-volatile components in the resin composition is preferably 30 to 95 mass%, more preferably 40 to 85 mass%. When the proportion of compound (B) is below the upper limit, the proportions of other components are high, so sufficient adhesion is obtained and the coating appearance is not insufficient. On the other hand, when the proportion of compound (B) is above the lower limit, adhesion is good and sufficient film-forming properties are ensured, resulting in a uniform coating film.
[0050] The total content of compounds (A) and (B) in the resin composition is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 97% by mass or more, and is 100% by mass or less, based on 100% by mass of the resin composition. The compounding ratio (A) / (B) (mass ratio) of the compounds (A) and (B) in the cured resin layer is preferably 10 / 90 to 50 / 50, more preferably 30 / 70 to 40 / 60. By having the compounding ratio (A) / (B) within the above range, a cured resin layer having good strength and transparency can be obtained, and desired adhesion can be obtained.
[0051] <Cured resin layer> The cured resin layer according to the present invention is formed from the above-mentioned resin composition. The thickness of the cured resin layer is preferably 0.002 μm or more and 1.0 μm or less, more preferably 0.005 μm or more and 0.25 μm or less, and even more preferably 0.02 μm or more and 0.10 μm or less. If the thickness of the cured resin layer is within the above range, precipitation of oligomer components can be suppressed and good antistatic properties can be imparted. The content of the cured resin layer composition in the cured resin layer is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more, and 100% by mass or less, based on 100% by mass of the cured resin layer. It can be assumed that unreacted compounds of various compounds of the resin composition, reacted compounds, or a mixture thereof are present in the cured resin layer.
[0052] <Method of manufacturing laminated polyester film for silicone adhesive (method of forming cured resin layer)> Next, a method for forming the cured resin layer constituting the laminated polyester film will be described. The method for forming the cured resin layer is not particularly limited, and any conventionally known coating method such as reverse gravure coating, direct gravure coating, roll coating, die coating, bar coating, curtain coating, etc. can be used. The cured resin layer can be formed by in-line coating or off-line coating. The drying and curing conditions are not particularly limited, and when the cured resin layer is formed by off-line coating, the heat treatment is usually performed at 80 to 200°C for 3 to 40 seconds, preferably at 100 to 180°C for 3 to 40 seconds. On the other hand, when the cured resin layer is provided by in-line coating, it is usually preferable to carry out heat treatment at 70 to 280° C. for 3 to 200 seconds as a guideline.
[0053] In the present invention, it is preferable to form the protective layer by in-line coating, which is a method of treating the surface of a polyester film during the film-forming process. In-line coating is a method of coating within the polyester film production process, specifically, a method of coating at any stage from melt extrusion of polyester to stretching, heat setting and winding up. Usually, coating is performed on any of the following: an unstretched sheet obtained by melting and quenching, a stretched uniaxially stretched film, a biaxially stretched film before heat setting, and a film after heat setting and before winding up. Although not limited to the following, for example, in sequential biaxial stretching, a method of coating a uniaxially stretched film stretched in the longitudinal direction (longitudinal direction) and then stretching in the transverse direction is particularly excellent. According to this method, film formation and cured resin layer formation can be performed simultaneously, which is advantageous in terms of production costs. In addition, since stretching is performed after coating, the thickness of the cured resin layer can be changed by the stretching ratio, and thin film coating can be performed more easily than with offline coating films. In addition, by providing a cured resin layer on the film before stretching, the cured resin layer can be stretched together with the polyester film, and the cured resin layer can be firmly attached to the polyester film. Furthermore, in the production of a biaxially stretched polyester film, by stretching the film while holding the ends with clips or the like, the film can be restrained in the longitudinal and lateral directions, and in the heat setting step, high temperatures can be applied while maintaining flatness and without wrinkles, etc. Therefore, since the heat treatment performed after coating can be performed at a high temperature that cannot be achieved by other methods, the film-forming properties of the cured resin layer are improved, the cured resin layer and the polyester film can be more firmly adhered to each other, and further, a strong cured resin layer can be formed, and performance such as adhesion to various functional layers that can be formed on the cured resin layer and resistance to moisture and heat can be improved.
[0054] When the cured resin layer is provided by in-line coating, it is preferable to produce a laminated polyester film by coating a cured resin layer composition, which is prepared by preparing an aqueous solution or aqueous dispersion of the above-mentioned series of compounds so that the solid content (total non-volatile components) is adjusted to approximately 0.1 to 50 mass %, onto a polyester film.
[0055] Regardless of whether off-line coating or in-line coating is used, heat treatment and irradiation with active energy rays such as ultraviolet rays may be used in combination as necessary. The polyester film constituting the laminated polyester film of the present invention may be previously subjected to a surface treatment such as a corona treatment or a plasma treatment.
[0056] The laminated polyester film for silicone adhesion of the present invention has a cured resin layer on at least one surface of the polyester film. The polyester film may have a cured resin layer on both sides. In addition, when the polyester film has a cured resin layer on one side, the polyester film may have another functional layer on the side opposite to the side on which the cured resin layer is formed. Examples of the other functional layer include an antifouling layer, a hard coat layer, and an antireflection layer.
[0057] From the viewpoint of handleability, the total thickness of the silicone adhesive laminated polyester film of the present invention is preferably 200 μm or less, more preferably 9 μm or more and 125 μm or less, even more preferably 12 μm or more and 125 μm or less, and even more preferably 25 μm or more and 125 μm or less.
[0058] <Film laminate> The film laminate of the present invention has a configuration in which another resin film or a glass substrate is laminated onto the cured resin layer of the above-mentioned laminated polyester film via a silicone adhesive layer.
[0059] (Silicone adhesive layer) The silicone adhesive may be any adhesive containing silicone as a main resin component. The "main component resin" means the resin that has the largest content (mass) among the resins that make up the pressure-sensitive adhesive. Examples of silicone adhesives include addition reaction type, peroxide curing type, and condensation reaction type silicone adhesives. Among them, addition reaction type silicone adhesives are preferably used from the viewpoint of being curable at low temperature in a short time. These addition reaction type silicone adhesives are cured when the adhesive layer is formed on the support. When an addition reaction type silicone adhesive is used as the silicone adhesive, the silicone adhesive may contain a catalyst such as a platinum catalyst. For example, the addition reaction type silicone pressure-sensitive adhesive can be prepared by, if necessary, adding a catalyst such as a platinum catalyst to a silicone resin solution diluted with a solvent such as toluene, stirring until homogeneous, coating the solution on a support, and curing the solution for 1 to 5 minutes at 100 to 130° C. If necessary, a crosslinking agent or an additive for controlling adhesive strength may be added to the addition reaction type silicone pressure-sensitive adhesive, or a primer treatment may be applied to the substrate film before the adhesive layer is formed.
[0060] Commercially available silicone resins for use in addition reaction type silicone pressure sensitive adhesives include, for example, SD4580PSA, SD4584PSA, SD4585PSA, SD4587LPSA, SD4560PSA, SD4570PSA, SD4600FCPSA, SD4593PSA, DC7651ADHESIVE, DC7652ADHESIVE, LTC-755, LTC-310 (all manufactured by Dow Corning Toray Co., Ltd.), KR-3700, KR-3701, KR-3704, X-40-3237-1, X-40-3240, Examples of suitable antibacterial agents include X-40-3291-1, X-40-3229, X-40-3323, X-40-3306, X-40-3270-1 (all manufactured by Shin-Etsu Chemical Co., Ltd.), AS-PSA001, AS-PSA002, AS-PSA003, AS-PSA004, AS-PSA005, AS-PSA012, AS-PSA014, PSA-7465 (all manufactured by Arakawa Chemical Industries Co., Ltd.), TSR1512, TSR1516, TSR1521 (all manufactured by Momentive Performance Materials, Inc.), and the like.
[0061] The thickness of the silicone adhesive layer (after drying) is preferably 1 to 100 μm, more preferably 5 to 80 μm, even more preferably 10 to 60 μm, and still more preferably 20 to 50 μm.
[0062] (Other resin films or glass substrates) The other resin film is preferably a resin film selected from the group consisting of a polyester film, a polyimide film, and a cyclic polyolefin film.
[0063] It is also preferable to provide a functional layer on the surface of the other resin film that is in contact with the silicone adhesive layer. The functional layer is preferably a release layer. The release layer preferably contains at least one type selected from the group consisting of a curable silicone resin, a fluorine-based compound, and a long-chain alkyl compound.
[0064] An example of the release layer is one having a structure sequentially including a first layer formed from a silicone composition containing, as a main component, a curable silicone that does not contain a fluorine substituent, and a second layer containing a component having a fluorine substituent.
[0065] Another example of the release layer is a layer formed from a silicone composition containing, as a main component, a curable silicone containing a fluorine substituent.
[0066] Furthermore, another example of the release layer is a layer formed from a silicone composition containing, as a main component, a curable silicone that does not contain a fluorine substituent.
[0067] From the viewpoint of handleability, the total thickness of the laminated film of the present invention is preferably 200 μm or less, more preferably 9 μm or more and 125 μm or less, even more preferably 12 μm or more and 125 μm or less, and particularly preferably 25 μm or more and 125 μm or less.
[0068] <Applications of laminated polyester film and film laminate> The laminated polyester film of the present invention can be suitably used as a substrate for optical components, etc., because of its excellent adhesion to silicone pressure-sensitive adhesives. It can also be suitably used as a protective material by bonding it to the surface of an optical component, etc., via a silicone pressure-sensitive adhesive. However, the use is not limited to this method.
[0069] The optical member may be a resin film selected from a polyester film, a polyimide film, or a cyclic polyolefin film, or a glass substrate. In the film laminate of the present invention, a silicone pressure-sensitive adhesive having good durability and transparency can be used. Therefore, by taking advantage of the heat resistance, cold resistance, weather resistance and high transparency that the silicone adhesive itself possesses, it can be suitably used in displays such as touch panels, and can be particularly suitably used in vehicle-mounted displays such as car navigation systems.
[0070] <Method of manufacturing film laminate> The method for producing the film laminate of the present invention is not particularly limited, but for example, the silicone adhesive layer forming liquid is applied to the cured resin layer of the silicone adhesive laminate polyester film of the present invention with an applicator to form a silicone adhesive layer, and then another resin film or a glass substrate is laminated onto the silicone adhesive layer to produce the film laminate of the present invention. The method for applying the silicone adhesive layer forming liquid is not particularly limited, and can be performed by a conventionally known method. In addition, as described above, the other resin film may have a functional layer on the surface that contacts the silicone adhesive layer.
[0071] The components in the cured resin layer can be analyzed by, for example, TOF-SIMS, ESCA, fluorescent X-ray analysis, or the like. EXAMPLES
[0072] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples within the scope of the present invention. The measurement and evaluation methods used in the present invention are as follows.
[0073] <Measurement and evaluation methods> (1) Intrinsic viscosity of polyester 1 g of polyester from which components incompatible with the polyester had been removed was precisely weighed out, dissolved in 100 mL of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and the viscosity was measured at 30°C using a viscosity (IV) measuring device (Rigo Co., Ltd., "VMS-022UPC·F10").
[0074] (2) Average particle size The laminated polyester films of the Examples and Comparative Examples were observed using a transmission electron microscope (TEM) (Hitachi High-Tech Corporation, "H-7650", acceleration voltage 100 kV), and the average particle size of 10 particles was taken as the average particle size.
[0075] (3) Thickness of the cured resin layer The surface of the cured resin layer of the laminated polyester film of the examples and comparative examples was treated with RuO 4 The sections were stained with fluorine and embedded in epoxy resin. The cross sections of the cured resin layers were then measured using a transmission electron microscope (TEM) (Hitachi High-Technologies Corporation, "H-7650", accelerating voltage 100 kV).
[0076] (4) Glass transition temperature (Tg) of polyester resin of compound (B) The glass transition temperature (Tg) was measured using a differential scanning calorimeter (PerkinElmer, "DSC7"). 6 mg of sample film was set in the DSC device, and the sample was heated from 0°C to 300°C at a rate of 10°C / min, and after being kept molten at 300°C for 5 minutes, it was quenched with liquid nitrogen. The quenched sample was heated from 0°C at a rate of 10°C / min, and the glass transition temperature was detected according to the method for reading DSC curves in JIS K7121:2012.
[0077] (5) Evaluation of adhesion and curing of silicone adhesive layer Silicone adhesive "KR-3704" (Shin-Etsu Silicone, solvent-added type) and catalyst "CAT-PL-50T" (Shin-Etsu Silicone) were mixed at 99.5:0.5 to prepare a silicone adhesive layer forming liquid. Next, the silicone adhesive layer forming liquid was applied to the cured resin layer side of the laminated polyester film of the examples and comparative examples with an applicator so that the thickness (after drying) was 5 μm, and the film was heat-treated at 100 ° C for 6 minutes to form a silicone adhesive layer. Next, an uncoated film (Mitsubishi Chemical Corporation, biaxially oriented polyethylene terephthalate film, T100 type, thickness 38 μm) was laminated on the silicone adhesive layer side to prepare an evaluation sample. The evaluation sample had a configuration of laminated polyester film (polyester film / cured resin layer) / silicone adhesive layer / uncoated film.
[0078] 5-1) Initial adhesion evaluation The uncoated film was peeled off from the evaluation sample stored for one day under conditions of 23°C and 50% RH, and the exposed surface of the silicone adhesive layer was cross-cut. The surface of the silicone adhesive layer in the cross-cut area was then rubbed five times with a finger to evaluate whether the silicone adhesive layer peeled off from the laminated polyester film according to the following evaluation criteria. The evaluation results are summarized in Table 1. 5-2) Evaluation of adhesion after aging The uncoated film was peeled off from the evaluation sample that had been stored at 23°C x 50% RH for one month, and the exposed surface of the silicone adhesive layer was cross-cut. The surface of the silicone adhesive layer in the cross-cut area was then rubbed five times with a finger to evaluate whether the silicone adhesive layer peeled off from the laminated polyester film, based on the following evaluation criteria. The evaluation results are summarized in Table 1. 5-3) Evaluation of the curing properties of silicone adhesive layer After storing the evaluation sample for one day at 23°C x 50% RH, the sample was peeled off and checked to see if the silicone adhesive layer was transferred to the uncoated film surface, based on the following evaluation criteria. The evaluation results are summarized in Table 1.
[0079] (Evaluation criteria for initial and aging adhesion) A: The silicone adhesive layer did not peel off from the laminated polyester film. B: The silicone adhesive layer peeled off slightly at the edges of the cross cuts, etc. C: The silicone adhesive layer was completely peeled off from the laminated polyester film. (Criteria for evaluation of the curing property of silicone adhesive layer) A: The silicone adhesive layer did not transfer to the uncoated film surface that was peeled off. B: A small amount of the silicone adhesive layer was transferred to the surface of the uncoated film that was peeled off. C: The silicone adhesive layer was transferred to the surface of the peeled uncoated film.
[0080] The polyester raw materials for the polyester films used in the examples and comparative examples are as follows:
[0081] <Production of polyester for polyester film> (Production method of polyester (1)) 100 parts by mass of dimethyl terephthalate and 55 parts by mass of ethylene glycol were used as starting materials, and 0.04 parts by mass of magnesium acetate tetrahydrate was placed in a reactor as a catalyst, and the reaction temperature was set to 150° C. The reaction temperature was gradually increased as methanol was distilled off, and after 3 hours, the reaction temperature reached 230° C. The reaction was then continued for another hour, and the transesterification reaction was essentially completed. 0.02 parts by mass of ethyl acid phosphate was added to this reaction mixture, and then 0.04 parts by mass of antimony trioxide was added to carry out a polycondensation reaction. At this time, the reaction temperature was gradually increased from 230°C to a final temperature of 280°C. The pressure was gradually reduced from normal pressure to a final temperature of 0.3 mmHg. After 4 hours had passed since the start of the reaction, it was confirmed from the change in the stirring power of the reaction tank that the intrinsic viscosity of the reactant had reached 0.65 dL / g, so the reaction was stopped and the polymer was discharged under nitrogen pressure to obtain polyester (1) with an intrinsic viscosity of 0.65 dL / g.
[0082] (Production method of polyester (2)) 100 parts by mass of dimethyl terephthalate and 45 parts by mass of ethylene glycol were used as starting materials, and 0.06 parts by mass of magnesium acetate tetrahydrate was placed in a reactor as a catalyst, and the reaction temperature was set to 150° C. The reaction temperature was gradually increased as methanol was distilled off, and after 3 hours, the reaction temperature reached 230° C. The reaction was then continued for another hour, and the transesterification reaction was essentially completed. After adding 0.03 parts by mass of ethyl acid phosphate to this reaction mixture, 0.3 parts by mass of silica particles with an average particle size of 2.7 μm dispersed in ethylene glycol and 0.03 parts by mass of antimony trioxide were added to carry out a polycondensation reaction. At this time, the temperature was gradually increased from 230°C to a final temperature of 280°C. The pressure was gradually reduced from normal pressure to a final temperature of 0.3 mmHg. After 4 hours had passed since the start of the reaction, it was confirmed from the change in the stirring power of the reaction tank that the intrinsic viscosity of the reactant had reached 0.65 dL / g, so the reaction was stopped and the polymer was discharged under nitrogen pressure to obtain polyester (2) with an intrinsic viscosity of 0.65 dL / g.
[0083] The following were used as raw materials for the resin composition for forming the cured resin layer (cured resin layer composition).
[0084] (Compound (A): Crosslinking agent) (A1): Epoxy compound Water-soluble polyglycerol polyglycidyl ether (A2): Carbodiimide compound Polycarbodiimide compound "Carbodilite SV-02" (carbodiimide equivalent: 430) (manufactured by Nisshinbo Co., Ltd.) (A3): Oxazoline compound Acrylic polymer with oxazoline groups and polyalkylene oxide chains Product name: "Epocross" (oxazoline group amount = 7.7mmol / g, manufactured by Nippon Shokubai Co., Ltd.) (A4): Melamine compounds Hexamethoxymethylolmelamine
[0085] (Compound (B): Polyester resin) (B1): A water dispersion of a polyester resin having a glass transition temperature (Tg) of 52°C, copolymerized with the following composition: Monomer composition: (acid component) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / / (diol component) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (molar ratio) (B2): A water dispersion of a polyester resin having a glass transition temperature (Tg) of 110°C, copolymerized with the following composition: Monomer composition: (acid component) 2,6-naphthalenedicarboxylic acid / 5-sodium sulfoisophthalic acid / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (molar ratio) (B3): A water dispersion of a polyester resin having a glass transition temperature (Tg) of 25°C, copolymerized with the following composition: Monomer composition: (acid component) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / / (diol component) ethylene glycol / diethylene glycol / triethylene glycol = 60 / 32 / 8 / / 45 / 45 / 10 (molar ratio) (B4): A water dispersion of a polyester resin having a glass transition temperature (Tg) of -20°C, copolymerized with the following composition: Monomer composition: (acid component) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / dodecanedioic acid / (diol component) ethylene glycol / 1,4-butanediol = 40 / 40 / 8 / 2 / / 60 / 40 (molar ratio)
[0086] (Other binder resins) (C1): Aqueous dispersion of urethane resin copolymerized with the following composition Monomer composition: isophorone diisocyanate / terephthalic acid / isophthalic acid / ethylene glycol / diethylene glycol / dimethylolpropanoic acid = 12 / 19 / 18 / 21 / 25 / 5 (molar ratio) (C2): Aqueous dispersion of acrylic resin polymerized with the following composition Monomer composition: Emulsion polymer of ethyl acrylate / n-butyl acrylate / methyl methacrylate / N-methylolacrylamide / acrylic acid = 65 / 21 / 10 / 2 / 2 (mass ratio) (emulsifier: anionic surfactant)
[0087] Example 1 A blend of polyester (1) and polyester (2) in a mass ratio of 82 / 18 was used as the raw material for layer A, and polyester (1) alone was used as the raw material for layer B, which were fed into an extruder, heated and melted at 285°C, and co-extruded to a thickness ratio of A / B / A=5 / 90 / 5 under extrusion conditions, with layer A being the outermost layer (surface layer) and layer B being the middle layer, and then cooled and solidified while being in close contact with a mirror-finished cooling drum with a surface temperature of 40-50°C to prepare an unstretched polyester film. This film was stretched 3.7 times in the longitudinal direction while passing through a group of heating rolls at 85°C to produce a uniaxially oriented polyester film. A cured resin layer composition shown in Table 1 below was applied to one side of this uniaxially oriented polyester film, and then this film was introduced into a tenter stretching machine and stretched 4.3 times in the width direction at 100°C. Further, after being subjected to a heat treatment at 230°C, a relaxation treatment was performed by 2% in the width direction to obtain a biaxially oriented laminated polyester film of Example 1 having a thickness of 50 μm and a cured resin layer with a thickness (after drying) of 0.05 μm.
[0088] (Examples 2 to 17) The same procedure as in Example 1 was carried out except that the cured resin layer composition was changed to the composition shown in Table 1, and laminated polyester films of Examples 2 to 17 were obtained.
[0089] (Comparative Examples 1 to 7) The same procedure as in Example 1 was carried out except that the cured resin layer composition was changed to the composition shown in Table 1, and laminated polyester films of Comparative Examples 1 to 7 were obtained.
[0090] [Table 1]
[0091] (Consideration) According to the results of the investigations conducted by the present inventors, it was found that the adhesion between the silicone adhesive layer and the cured resin layer, which is formed from a crosslinking agent and a polyester resin of a specific composition, is particularly good. Of these, it has been found that a combination of an epoxy resin and a polyester resin in particular makes it possible to simultaneously improve adhesion to the silicone adhesive layer and suppress inhibition of curing of the silicone adhesive layer. In addition, since the silicone adhesive layer used in this evaluation is of a weak adhesive type, it is presumed that the adhesive layer side is less likely to have a further adhesiveness improving effect than the normal type. However, it is considered that a significant adhesiveness improving effect was obtained in that the adhesive layer maintains good adhesiveness even after one month has passed since it was applied onto the cured resin layer. The cured resin layer of the present invention is characterized by having a composition (non-silicone-based) different from the conventional primer (silicone-based) for silicone adhesive layers, and being a thin film (coating thickness (after drying) of 0.1 μm or less).
Claims
1. A polyester film is provided on at least one surface thereof with a cured resin layer comprising a cured resin layer composition containing the following compounds (A) and (B): The cured resin layer composition further comprises at least one compound selected from the group consisting of an oxazoline compound and a melamine compound. (A) At least one crosslinking agent selected from the group consisting of epoxy compounds and carbodiimide compounds. (B) A polyester resin having a glass transition temperature (Tg) of 0° C. or higher.
2. 2. The laminated polyester film for silicone adhesion according to claim 1, wherein the compound (B) is a polyester resin containing a dicarboxylic acid component having 10 or less carbon atoms as an acid component.
3. 3. The silicone adhesive laminate polyester film according to claim 1, wherein the compound (B) is a polyester resin containing, as a diol component, ethylene glycol and at least one selected from 1,4-butanediol, diethylene glycol and triethylene glycol.
4. 4. The laminated polyester film for silicone adhesion according to claim 1, wherein the compound (B) is a polyester resin containing a polycyclic compound as an acid component.
5. The laminated polyester film for silicone adhesion according to any one of claims 1 to 4, wherein the compound (A) and the compound (B) have a compounding ratio (A) / (B) (mass ratio) of 10 / 90 to 50 / 50.
6. 6. A film laminate comprising the laminated polyester film according to claim 1, and another resin film or a glass substrate laminated onto the cured resin layer of the laminated polyester film via a silicone adhesive layer.
7. The film laminate according to claim 6 , wherein the other resin film is selected from the group consisting of a polyester film, a polyimide film, and a cyclic polyolefin film.
8. The film laminate according to claim 6 or 7, further comprising a functional layer provided on a surface of the other resin film that is in contact with the silicone adhesive layer.
9. The film laminate according to claim 8 , wherein the functional layer is a release layer.
10. 10. The film laminate according to claim 9, wherein the release layer comprises at least one selected from the group consisting of a curable silicone resin, a fluorine-based compound, and a long-chain alkyl compound.
11. The film laminate according to any one of claims 6 to 10, having a total thickness of 200 µm or less.
12. The pressure-sensitive adhesive laminated polyester film according to any one of claims 1 to 5, which is for use in a display.
13. The film laminate according to any one of claims 6 to 12, which is for a display.
14. The film laminate according to claim 13, which is for use in a vehicle.
Citation Information
Patent Citations
Readily adhering polyester film for optical use
JP2003049011A
Silicone composition and adhesive film bearing adhesive layer obtained from the composition
JP2006152266A
Primer composition for silicone pressure-sensitive adhesive, laminate, and silicone pressure-sensitive adhesive tape
JP2013139509A
Thin film support sticking film
JP2020128484A